Kondisi Psikologis Ibu Yang Mengalami Baby Blues Pasca Melahirkan - Arrouf, Azifah; Rahayu, Sri Putri (Universitas Medan Area, 2024)
Baby Blues Syndrome is known as a mild affective disorder syndrome characterized by symptoms such as sad reactions or dysphoria, crying, irritability, anxiety, feelings of instability, tendency to blame themselves, feelings of fatigue, sleep disturbances, and appetite disorders. Postpartum blues is a feeling of sadness experienced by mothers giving birth, this can occur in all postpartum mothers of any ethnicity and race and can occur in primiparous and multiparous mothers. The psychological impact that occurs is that postpartum mothers experience anxiety and fear due to conditions that change drastically, for example in mothers who have just given birth to their first child will feel a very drastic change in conditions and also the lack of support from their husband and family also makes a mother feel ignored and feel lonely. It can cause the mother to blame the child's presence and also be a factor of the social environment that comments too much so that the mother feels like a failure in taking care of her child. The method used in this writing is library research. The purpose of writing this scientific work is to understand more about the issue of baby blues syndrome. In addition, the purpose of writing this scientific work is to provide information to people from various circles about the importance of knowing the impact of baby blues syndrome and the symptoms that appear to be more aware of the closest people. From this study, the authors found that the conditions experienced by mothers affected by baby blues syndrome are anxiety, sadness, loneliness, feeling guilty about the baby, and so on. This can occur due to a lack of support from the family or a lot of talk or negative views of the mother and baby that cause negative thoughts to arise in the mother.